2021
DOI: 10.1016/j.jvs.2021.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of silent coronary ischemia with selective coronary revascularization might improve 2-year survival of patients with critical limb-threatening ischemia

Abstract: Background: Patients with critical limb-threatening ischemia (CLTI) have had poor long-term survival after lower extremity revascularization owing to coexistent coronary artery disease. A new cardiac diagnostic test, coronary computed tomography-derived fractional flow reserve (FFR CT ), can identify patients with ischemia-producing coronary stenosis who might benefit from coronary revascularization. We sought to determine whether the diagnosis of silent coronary ischemia before limb salvage surgery with selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…18,25 Similarly, it has been shown that lower-extremity revascularization can be performed safely despite preoperative FFR CT evidence of silent coronary ischemia with long-term survival benefit with postoperative coronary revascularization. 16,17 The 80% reduction in the risk of cardiac death and the 84% reduction in the risk of MI associated with elective coronary revascularization in our study are not surprising given the extent and severity of asymptomatic coronary ischemia in the FFR CT -guided group. More than half of patients (57%) had one or more ischemia-producing coronary lesions, and 44% of patients had severe coronary ischemia with FFR CT values below 0.75.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…18,25 Similarly, it has been shown that lower-extremity revascularization can be performed safely despite preoperative FFR CT evidence of silent coronary ischemia with long-term survival benefit with postoperative coronary revascularization. 16,17 The 80% reduction in the risk of cardiac death and the 84% reduction in the risk of MI associated with elective coronary revascularization in our study are not surprising given the extent and severity of asymptomatic coronary ischemia in the FFR CT -guided group. More than half of patients (57%) had one or more ischemia-producing coronary lesions, and 44% of patients had severe coronary ischemia with FFR CT values below 0.75.…”
Section: Discussionmentioning
confidence: 57%
“…15 This strategy of selective coronary revascularization after recovery from surgery, in addition to optimal medical therapy (OMT), resulted in fewer cardiovascular deaths and MIs and improved 2-and 3-year survival compared with standard cardiac evaluation and care. 16,17 We performed a similar study in patients undergoing CEA. Preoperative cardiac evaluation of patients with no known CAD using CTA and FFR CT revealed a high prevalence of asymptomatic coronary ischemia and demonstrated the potential value of FFR CT -guided coronary revascularization in reducing the risk of adverse cardiac events.…”
mentioning
confidence: 99%
“…Patients with CLTI have multiple comorbidities, and operation risks are elevated. 24 , 25 Moreover, young CLTI patients have a high prevalence of DM, poor glycemic control, coronary artery disease, smoking, renal insufficiency, and high WIfI stage. 26 On the other hand, non-ambulatory associated conditions such as a higher BMI are less common in younger CLTI patients compared to older age groups, 26 which therefore enables an active revascularization strategy to be used.…”
Section: Discussionmentioning
confidence: 99%